PERBANDINGAN KADAR MALONDIALDEHID SERUM PADA BERBAGAI DERAJAT KEPARAHAN AKNE VULGARIS Studi pada Populasi Pria di Yogyakarta - , Aprilina Dwi Sulistyowati ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Acne is an inflamative chronic skin disease which has multifactorial pathogenesis such as sebaceous hyperplasia, follicular hiperkeratinization, hipercolonization of Propionibacterium acnes, and inflammation. Oxidative stress especially lipid peroxidation in purpose is one trigger inflammation in acne vulgaris. Oxidative stress is also influenced by environmental factors and ultraviolet (UV) light. The UV radiation in Yogyakarta is relatively higher compare in other region. Effect of high UV will increase lipid peroxidation in the skin so that the malondialdehyde (MDA) as the outcome of lipid peroxidation will be increased and eventually lead to inflammation in acne. This research was conducted to compare the levels of serum MDA in various degrees of severity of acne vulgaris in Yogyakarta. An observasional, descriptive, and cross sectional study was conducted in Yogyakarta with a consecutive sampling method to achieve 60 male acne subject. The combined acne severity classification (CASC) method is used to determine the severity of acne. Statistical analysis uses one way analysis test of variance and Spearman's rho correlation test with a significance value of p<0.05. Sixty male acne subjects were divided into 3 groups, namely mild, moderate, and severe acne. Each of these group consists of 20 subjects. Mild acne showed MDA levels lower than moderate (p= 0.002) and severe acne (p=0.000) and moderate acne also lower than severe acne (p=0.000). There were strong positive correlation between MDA serum with acne lesion total count (p=0.000